Spatial Analysis of Dengue Hemorrhagic Fever based on Influencing Factors in Jombang, 2014–2018 - Retno Tri Hastuti; Lucia Yovita Hendrati (Universitas Airlangga, 2021)
Background: Jombang District is an endemic area of dengue hemorrhagic fever (DHF). Purpose: The aim of this study was to spatially analyze various factors simultaneously (multivariate analysis) in relation to the incidence of DHF in Jombang District during the period 2014–2018. The factors studied were population density, larvae free index, rainfall, coverage of healthy homes, and healthy lifestyle coverage. Methods: The research was conducted as an observational study with an ecology research design. The data were secondary data from the Health Office and Statistic Central Bureau of Jombang District. The population consisted of 21 sub-districts in Jombang District in 2014–2018. The sample used the total population. The data analysis tool used in this study was GeoDa regression Moran's I software. Results: The bivariate analysis showed that there was a correlation between larvae free index (p = 0.04), healthy lifestyle coverage (p = 0.02), rainfall intensity (p = 0.20), population density (p = 0.07), and coverage of healthy houses (p = 0.22) with DHF incidence. According to Moran's I for spatial dependence (multivariate analysis), showed that there was a correlation between all the variables and DHF (p = 0.03). Conclusions: The variables of larvae free index and healthy lifestyle coverage related to the Incidence Rate (IR) of DHF cases. There was no correlation between IR and variable population density, rainfall, or coverage of healthy homes. Various spatial factors are simultaneously related to IR, even though only two variables are shown to be related to IR in the bivariate analysis.